Aiden Lundien: capstone - Lundien, Aiden, artist (Colorado State University. Libraries, 2025)
The artist's statement: My name is Aiden Lundien, and I'm an aspiring filmmaker based in Steamboat Springs, Colorado. Ever since I was a child, I was enamored by the art of filmmaking, and it was instrumental to my development as a person. Everybody is born under different circumstances. Our upbringing is unique, where we were born is unique, and who we have grown to be is unique. The goal of civilization and progress is to reach out and empathize with other people and discover what makes them tick, and what they care about. Movies have helped me connect with others, and taught me how to understand how another person is feeling. Exploring these universal connections and emotions has become my primary goal as an artist. I want to tell stories that are raw and bring people together to feel something, and I explore these connections through digital and analog filmmaking/photography. I don't strive to create because it's cute. I strive to create because I'm a member of the human race. Art, beauty, romance, love; these are the things we stay alive for.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art